SYNTHESIS AND EVALUATION OF ANTIDIABETIC PROPERTIES OF A ZINC MIXED LIGAND COMPLEX IN HIGH-FAT DIET - LOW-DOSE STREPTOZOTOCIN-INDUCED DIABETIC RATS - Koothappan, Muruganantham; Devi Vellai, Roshana; Pillai Subramanian, Iyyam; Sorimuthu Pillai, Subramanian (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Due to the multifactorial and multisystemic nature of diabetes mellitus (DM), it is often treated with a combination of therapeutic agents. Earlier, we have synthesized and characterized several organozinc complexes and evaluated their safety and antidiabetic properties in experimental DM. In the present study, a new zinc mixed ligand (metformin-3-hydroxyflavone) was synthesized and characterized by various spectral studies and its antidiabetic properties were evaluated in high-fat diet (HFD) fed – low-dose streptozotocin (STZ)-induced Type 2 D (T2D) in rats. Methods: The zinc mixed ligand complex was characterized by spectral studies. The toxicity and dosage fixation studies were carried out as per OECD guidelines 423. HFD fed low-dose STZ-induced T2DM in rats was used as the experimental model. The hypoglycemic efficacy of the complex was evaluated through oral glucose tolerance test, homeostasis model assessment of insulin resistance (IR), QUICK I and by determining the status of important biochemical parameters. The activities of marker enzymes such as aspartate aminotransferase, alanine aminotransferase, and alkaline phosphatase were assayed. Metformin was used as a standard drug. Results: The spectral data evidenced the synthesis of a new zinc mixed ligand complex. The biochemical studies evidenced that the oral administration of the complex at a concentration of 10 mg/kg b.w/rat/day for 30 days to diabetic rats significantly improved the glucose homeostasis which was comparable to metformin treatment (50 mg/kg b.w). Conclusion: The zinc mixed complex possesses significant antidiabetic properties in ameliorating IR and stimulatory properties.